THE IMPACTS OF SETTLEMENT EXTENSION ON SOIL RESOURCES: A CASE STUDY IN DRENICA RIVER BASIN (KOSOVO) - Valbon Xh. BYTYQI (Universitas Pendidikan Ganesha, 2018)
Rapid extension of settlements in Kosovo has made major changes in land use and land cover. Migration of population towards plains has reduced the number of inhabitants in hilly-mountainous areas where low fertile soils are found. Significant part of agricultural land are changed from primary destination, and agricultural potentials are reduced. Urbanization in many cases is made in unplanned way, and in our study area in Drenica River basin are observed land degradation forms and other environmental transformations where in some cases the risk of flooding increased and floods appeared. This study about Drenica River basin will discuss aspects of the influence of morphology, water flows, and the land capability in the distribution of population, and will be a contribution to sustainable urbanization of settlements and agricultural land preservation. In order to accomplish the research are used satellite images, maps of different years, and the census data for the purpose of better coverage that has influence in the process of urbanization on soil resources in Drenica River basin (Kosovo).